Language, Identity, and Globalization: Code-Switching Practices in Multilingual Academic Communities - Assel Aben; Saule Zeinolla (International Journal of Social Sciences, Language, and Education, 2026)
This study examines code-switching practices in multilingual academic communities by foregrounding the interconnected roles of language, identity, and globalization. Drawing on a qualitative interpretive approach grounded in theoretical and analytical inquiry, the research synthesizes established sociolinguistic and discourse-based scholarship to explore how code-switching operates within academic settings. The findings indicate that code-switching functions as a strategic resource through which academics negotiate professional identity, epistemic authority, and social affiliation across diverse communicative contexts. In globalized academic environments, language alternation reflects the influence of linguistic markets, digital communication, and transnational mobility, reshaping norms of scholarly interaction. The analysis further highlights how code-switching supports pedagogical processes, facilitates interaction in multilingual classrooms, and enhances accessibility in digital academic spaces. Rather than undermining academic rigor, code-switching contributes to the richness and adaptability of scholarly discourse. This study concludes that recognizing code-switching as an integral feature of multilingual academic life is essential for rethinking language ideologies, institutional policies, and future research on global academic communication.